Bill of rights for the 21st century: some lessons from the Internet Bill of Rights movement - Yilma, Kinfe Micheal (The international journal of human rights, 2022)
This article examines the extent to which the so called the 'Internet Bill of Rights' (IBRs) movement might offer useful lessons in building bills of rights for the 21st century. Informed by a selection of initiatives for IBRs and theories of rights, it considers possible lessons that may assist in building a bill of rights that possesses substantive and procedural legitimacy. It submits that designing a bill of rights that builds, like the IBRs movement, on best practices that enjoy some level of consensus and embodies standards that are fit for purpose in the digital age would earn some substantive legitimacy. It further highlights that procedural legitimacy of a modern bill of rights might be higher if its lawmaking process embraces a multi-stakeholder approach that is reinforced through crowdsourcing mechanisms. The article, however, cautions about aspects of the IBRs project that might work against the aim of enhancing legitimacy of a bill of rights. These include issues of desirability, feasibility and the incongruent interplay of IBRs with international human rights law as well as the inherent limitations of multi-stakeholderism and crowdsourcing in lawmaking.